(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 1995)
We consider a Lagrangian differential system. The celebrated theorem of Lagrange-Dirichlet ensures that a stationary solution of this system is stable, provided that the corresponding critical point of the potential function is a proper local maximum.